Long-term outcomes of en-bloc renal transplantation from paediatric donors into adult recipients. Issue 1 (February 2019) - Considine, S.W.; Davis, N.F.; McLoughlin, L.C.; Mohan, P.; Forde, J.C.; Power, R.; Smyth, G.; Little, D.M.
Abstract: Introduction: Transplant units are exploring strategies to increase the availability of donor kidneys. The use of en-bloc kidney transplantation (EBKT) from paediatric donors represents one potential solution. We present our long-term experience with paediatric EBKT among adult recipients. Methods: Twenty-three paediatric to adult EBKTs were performed by the Irish National Kidney Transplant Service between 1990 and 2016. The primary outcome variable was long-term en-bloc allograft survival rate. Secondary outcome variables were incidence of allograft thrombosis, incidence of delayed graft function, overall patient survival and serum creatinine at most recent follow-up. Outcomes were compared to single kidney transplant recipients from the same time period. Results: Mean donor age was 1.8 ± 0.97 years (range: 7 months to 3 years). Recipient age was 46 ± 12 years. Mean follow-up was 133 ± 64 months (range: 36–264). Overall graft survival was 100%, 91% and 80% after 1, 5 and 10 years respectively, compared to 92%, 79% and 61% in single kidney transplant recipients ( p  = 0.04). There were 5 cases of allograft failure, 3 due to death from unrelated causes. Median time to graft failure was 108 months (range: 36–172). Mean serum creatinine was 72.6 ± 21.6 μmol/l after the follow-up period. There were no cases of graft thrombosis or delayed graft function. Overall survival was 96.4%, 88.0%, 76.23% and 50.5% at 1, 5, 10 and 20 years respectively. Conclusion: En-bloc paediatric kidney transplantation is associated with excellent long-term allograft and patient survival and is a feasible strategy for increasing the transplant donor pool in carefully selected recipients.